Alcohol and polyol dehydrogenases are both divided into two protein types, and structural properties cross-relate the different enzyme activities within each type. - Jörnvall, H (1981)
Sorbitol dehydrogenase from sheep liver shows similarities to mammalian and yeast alcohol dehydrogenases. Comparisons based on peptides from segments of sorbitol dehydrogenase reveal that homologous regions with 38% identity include two ligands to the active site zinc atom in liver alcohol dehydrogenase, as well as further important residues. Similarities in in other regions are less extensive, exactly as they are between different alcohol dehydrogenases. In all aspects, sorbitol dehydrogenase appears as a typical member of the alcohol dehydrogenase family. On the other hand, alcohol dehydrogenase from Drosophila, which has a shorter subunit, is not closely related to either of these enzymes, except for a region that probably corresponds to the first part of the coenzyme binding domain in many dehydrogenases. Instead, Drosophila alcohol dehydrogenase in its supposed catalytic region shows similarities toward Klebsiella ribitol dehydrogenase, which also has a small subunit. It may be concluded that both alcohol and polyol dehydrogenases show two types of protein subunit, reflecting an early subdivision of polypeptide types into "long" and "short" subunits rather than into different enzymatic specificities or quaternary structures. The relationships explain known properties of all these enzymes and provide insight into functional mechanisms and evolutionary interpretations.